Psychological therapy for people with tinnitus: a scoping review of treatment components - Thompson, Dean M; Hall, Deborah A.; Walker, Dawn-Marie; Hoare, Derek J. (Lippincott, Williams & Wilkins, 2016)
Background: Tinnitus is associated with depression and anxiety disor- ders, severely and adversely affecting the quality of life and functional health status for some people. With the dearth of clinical psychologists embedded in audiology services and the cessation of training for hearing therapists in the UK, it is left to audiologists to meet the psychological needs of many patients with tinnitus. However, there is no universally standardized training or manualized intervention specifically for audiolo- gists across the whole UK public healthcare system and similar systems elsewhere across the world.